The origin of early-type runaway stars from open clusters - Bhat, Aakash; Irrgang, A.; Heber, U. (Astronomy & Astrophysics, 2022)
Runaway stars are ejected from their place of birth in the Galactic disk, with some young B-type runaways found several tens of kiloparsecs from the plane traveling at speeds beyond the escape velocity, which calls for violent ejection processes. Young open clusters are a likely place of origin, and ejection may be either through N-body interactions or in binary supernova explosions. The most energetic events may require dynamical interaction with massive black holes. The excellent quality of Gaia astrometry opens up the path to study the kinematics of young runaway stars to such a high precision that the place of origin in open stellar clusters can be identified uniquely even when the star is a few kiloparsecs away. We developed an efficient minimization method to calculate whether two or more objects may come from the same place, which we tested against samples of Orion runaways. Our fitting procedure was then used to calculate trajectories for known runaway stars, which have previously been studied from HIPPARCOS astrometry as well as known open clusters. For runaways in our sample we used Gaia data and updated radial velocities, and found that only half of the sample could be classified as runaways. The other half of the sample moves so slowly (< 30 km s(-1)) that they have to be considered as walkaway stars. Most of the latter stars turned out to be binaries. We identified parent clusters for runaways based on their trajectories. We then used cluster age and flight time of the stars to investigate whether the ejection was likely due to a binary supernova or due to a dynamical ejection. In particular we show that the classical runaways AE Aurigae and mu Columbae might not have originated together, with mu Columbae having an earlier ejection from Collinder 69, a cluster near the ONC. The second sample investigated comprises a set of distant runaway B stars in the halo which have been studied carefully by quantitative spectral analyses. We are able to identify candidate parent clusters for at least four stars including the hyper-runaway candidate HIP 60350. The ejection events had to be very violent, ejecting stars at velocities as large as 150-400 km s(-1).
CRIS-Team WoS Importer:2022-07-22